2016
DOI: 10.1111/1365-2745.12618
|View full text |Cite
|
Sign up to set email alerts
|

Quercus suber dieback alters soil respiration and nutrient availability in Mediterranean forests

Abstract: 1. An increase in tree mortality rates has been recently detected in forests world-wide. However, few works have focused on the potential consequences of forest dieback for ecosystem functioning. 2. Here we assessed the effect of Quercus suber dieback on carbon, nitrogen and phosphorus cycles in two types of Mediterranean forests (woodlands and closed forests) affected by the aggressive pathogen Phytophthora cinnamomi. We used a spatially explicit neighbourhood approach to analyse the direct effects of Q. sube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 104 publications
3
19
0
Order By: Relevance
“…Our models showed a negative effect of pathogen-driven mortality on P availability, at least in terms of labile P after incubations. This result is in agreement with previous field studies where reductions in P were detected in areas affected by P. cinnamomi (Ávila et al 2016;Shearer et al 2009). This reduction may be explained by a decrease in the root activity in soils under defoliated and dead trees, due to the importance of root exudates in regulating P availability (Schneider et al 2001).…”
Section: Accepted Articlesupporting
confidence: 93%
See 1 more Smart Citation
“…Our models showed a negative effect of pathogen-driven mortality on P availability, at least in terms of labile P after incubations. This result is in agreement with previous field studies where reductions in P were detected in areas affected by P. cinnamomi (Ávila et al 2016;Shearer et al 2009). This reduction may be explained by a decrease in the root activity in soils under defoliated and dead trees, due to the importance of root exudates in regulating P availability (Schneider et al 2001).…”
Section: Accepted Articlesupporting
confidence: 93%
“…context-dependent (Ávila et al 2016;Cherubini et al 2002;Shearer et al 2009). Moreover, gaps opened after tree death will be very likely occupied by coexistent drought-tolerant shrubs not affected by the pathogen (Ibáñez et al 2017), which might lead the system to a condition of arrested succession for at least several decades (Acácio et al 2007).…”
Section: Accepted Articlementioning
confidence: 99%
“…In ICP data for European forests some other not controlled factors may have also contributed to decrease more foliar P than N concentration. The frequency and intensity of some forest pests have increased 62,63 , so biotic factors not controlled in this study could have also favoured the P-uptake drop 64 . Moreover, soil P availability tends to decrease through time by natural processes 65 whereas N availability can continuously be maintained or increase by continuous loads of N deposition and N 2 -fixation.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, the microbial respiration could increase around vigorous trees as a result of higher root exudation rates and leaf and fine root litter supply to the soil [14]. In support of this reasoning it has been observed that variables related with photosynthetic C uptake, such as the leaf area index, sap flow, tree size, or tree proximity to and live tree basal area around R s sampling locations are positively related to R s [11,[15][16][17][18][19][20]. Nevertheless, R s can be relatively homeostatic across successional stages or after perturbations [8,[21][22][23].…”
Section: Introductionmentioning
confidence: 83%
“…However, complex plant-soil-climate interactions mediate tree mortality impacts on R s [10]. For example, Ávila et al [11] found that the effect of tree decline on soil variables differed in woodlands and closed forests, varied between seasons, and was higher as declining trees were larger.…”
Section: Introductionmentioning
confidence: 99%